The ‘Almost Completed House’: An Introduction to the Economic and Monetary Union - Marinkás, György (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
The first part of this chapter will focus on the asymmetric nature of the Economic and Monetary Union and the lack of proper supervision in its initial form. The second part will elaborate on how an adequate supervision system – the Banking Union – was created after the 2010 Greek sovereign debt crisis. This chapter introduces the phases of the creation of the Banking Union and its already-functioning three pillars and examines their roles by analysing three main sources: the case-law of the Court of Justice of the European Union, the reviews of European Union institutions (or reviews completed under their aegis), and scholarly opinions. The third part focuses on three sets of crisis management strategies of the European Central Bank: those enacted in response to the Greek sovereign debt crisis, those enacted in response to the negative economic effects of the COVID-19 pandemic, and those enacted in response to the most recent issue, the consequences of the Russo-Ukrainian War. Regarding the Greek sovereign debt crisis, this section dispenses with introducing the related monetary measures in detail since very rich literature on this topic already exists; instead, the focus is on the legal disputes around the response, especially the Public Sector Purchase Program of the European Central Bank. Keywords: Economic and Monetary Union, Eurozone, European Central Bank, Banking Union, Single Supervisory Mechanism, Single Resolution Mechanism, Public Sector Purchase Program, COVID-19, Russo-Ukrainian War, ultra vires